Radio Call-In Shows on Intimate Issues in Benin: "Crossroads of Sentiments". (9th April 2014) - Grätz, Tilo
Abstract: The article focuses on the growing prevalence of radio call-in shows in the Republic of Benin that discuss topics such as sexuality and intimacy that are taboo in other settings. The popularity of this emerging format exemplifies current processes of appropriation of electronic media in West Africa, including its impact on contemporary public communication. The article argues that the current public prominence of these programs corresponds to considerable shifts in the media landscape that are enabled by a variety of factors, including an increasing expertise among presenters and technicians and the influence of mobile phones.